(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2007)
Despite the popularity of evolutionary thinking across the intellectual landscape, existential therapy seems to not to have engaged with it a great deal. This paper argues that evolutionary theory can enrich our understanding of people and their lives – especially in relation to the ontological givens people face. It is suggested that a greater engagement with his theory might prompt thinking about a more holistic way of understanding our clients, rather than running the risk many psychotherapists face of getting stuck in the ghetto of one particular model.